HARDINESS PADA WANITA KARIR SINGLE PARENT YANG MEMILIKI ANAK TUNARUNGU - Zwagery, Rika Vira; Hikmatul, Hikmatul; Husna, Aridha (Jurnal Psikologi : Media Ilmiah Psikologi, 2017)
Women who work as well as single parents for children with special needs Deaf certainly has a variety of challenges, duties and responsibilities that must be lived, so do not rule out that women single parent careers who have children with hearing impaired can experience stress in undergoing the double role. In the face of this stressful situation, hardiness is required that is a personality trait that can affect the individual about how he sees a stressful situation and determine an effective response. This study aims to determine the description of hardiness in single parent career women who have children with hearing impairment and what factors influence it. The subject of this study was a 53-year-old woman with a role as a career woman as well as single parent who have children with hearing impairment. This study uses qualitative methods by conducting semi-structured interview techniques and non-participant observation in the data collection. The results of this study indicate that subjects have high hardiness which is described through 3 aspects of the existence of commitment, control, and challenges. The dominant factor affecting the hardiness of the subject is the acceptance of a good self in the subject.Â Keywords: hardiness, career woman, single parent, deaf